POLA PERGESERAN NILAI KEARIFAN LOKAL SISTEM LADANG BERPINDAH PADA MASYARAKAT ARFAK - Yuliana Ataribaba; Iwan Setiawan; Trisna Insan Noor (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Shifting cultivation is a form of traditional agricultural system that has been institutionalized and entrenched in the Arfak tribe. As a local wisdom, a shifting cultivation system is important to maintain in order to protec of local food security. The purpose of this study is to describe shifting cultivation patterns, identify local wisdom values (Igya Ser Hanjob); and analyze the factors that influence the shift of local wisdom values. For this reason, using a quantitative design and survey method. Primary data collected from interviews with 78 respondence using questionnaires instument, were analyzed using descriptive statistics. The results of the study revealed that shifting cultivation patterns had undergone a shift. Shifts occur at the time of planting and the range (area) of farming. Regarding shifting fields, the Arfak tribe has a value of hereditary local wisdom called Igya Ser Hanjob (especially dear to customary land and protecting forests). The shift was influenced by population pressure, oil palm plantations, family gardens, other clan estates, transmigrants and expansion of infrastructure. The recommendation is to protect community land and local wisdom together, through the integration of formal regulations with local (custom) agreements.